2019
DOI: 10.1108/mf-09-2018-0442
|View full text |Cite
|
Sign up to set email alerts
|

The effect of managerial horizon on cash holdings

Abstract: Purpose US corporations are now sitting on an enormous stockpile of cash. Instead of investing their resources and creating jobs, the firms are holding on to excess cash. Academicians and practitioners alike have tried to fathom the reasons why companies are holding on to so much cash. Numerous studies have talked about the various motives for holding cash. Many researchers have tried to correlate excess cash holding with particular firm characteristics. The purpose of this paper is to study the correlations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
(43 reference statements)
0
0
0
Order By: Relevance
“…Therefore, H3 is rejected. The six regressions above align with the research conducted by Guha and Rahim (2019), who found that CEO tenure has no effect on cash holdings.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Therefore, H3 is rejected. The six regressions above align with the research conducted by Guha and Rahim (2019), who found that CEO tenure has no effect on cash holdings.…”
Section: Discussionsupporting
confidence: 82%
“…(Orens & Reheul, 2013) and Mun et al (2017) also reported that older CEOs manage cash with precautionary motives and are less concerned with opportunities to increase cash. In contrast, Guha and Rahim (2019) stated that younger CEOs have more money than older CEOs. Older CEOs hold less cash because as CEOs get older, they may be motivated by the idea of leaving a lasting legacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation